The influence of marketing, non marketing and demographic factors on pre-purchase stage of consumer decision-making process for private college in Malaysia / Nooraini Mohamad Sheriff - Mohamad Sheriff, Nooraini (2005)
Studies on the pre-purchase stage of consumer decision making process have been done in isolation by establishing the association between selected external (marketing mix and non marketing), individual factors (demographics) and consumer decision making process. The highly competitive state coupled with numerous challenges faced by private colleges has propelled this decision to ascertain comprehensively the influences of these external and individual factors on the pre-purchase stage of consumer decision making process. The objective of this study is to determine consumer's perceived influence of the marketing mix strategies, non marketing factors and demographics on their pre-purchase process for private colleges. The importance of marketing mix, non marketing factors and demographics in influencing consumer's pre-purchase stage of decision making has been well supported by literature. Eight marketing mix strategies for private colleges are service product, pricing, placing, promotion, people, process, physical evidence and service performance outcome. Non marketing factors included social class, family and reference group. Four demographic factors included are gender, age, economic situation and ethnicity. Pre-purchase stage of consumer decision making process encompassed problem recognition, perceived risk, information search and evaluation ofchoice alternatives. The theoretical framework ofthis study treated the marketing, non marketing and demographics as independent variables and pre-purchase stage ofconsumer decision making process as dependent variable. The study hypothesized that there were independent relationships between marketing mix, non marketing factors, demographics and pre-purchase stage of consumer decision making process. It was also hypothesized that there were integrated relationships among marketing mix, non marketing factors, demographics and pre-purchase stage of consumer decision making process. This study expanded knowledge on the relationship between marketing mix, non marketing factors and pre-purchase process by relating them to demographics. The five hypotheses advanced were supported. A total of 120 multi-disciplined private colleges listed in Wencom Higher Education Guide were taken as samples for this study. The drop-off and mail survey methods employed to solicit the needed responses yielded a response rate of 62%. Correlation, multiple regression, bivariate and multivariate cross-tabulation were used for data analysis. The SPSS program was used to test for reliability of the instrument and normality of distribution. Content validity too was performed on the instrument. The fmdings showed that people, physical evidence and performance outcome are the marketing mix perceived to be most important in influencing the pre-purchase process. Reference group was the most important non marketing factor displaying a similar relationship. Ethnicity was the only demographics associated with elements of the pre-purchase stage of consumer decision making process. Overall this study supports the tlotion that marketing mix strategies, non marketing factors and demographics do influence consumer's pre-purchase stage of decision making process as depicted by Lancester and Massingham (2001), Schiffinan and Kanuk (1990, 2000) and Engel, Blackwell and Miniard (1995).